2015
DOI: 10.1002/hipo.22492
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of forebrain and hippocampal dopamine 1-class receptors, D1R and D5R, in spatial learning and memory

Abstract: Activation of prefrontal cortical (PFC), striatal, and hippocampal dopamine 1-class receptors (D1R and D5R) is necessary for normal spatial information processing. Yet the precise role of the D1R versus the D5R in the aforementioned structures, and their specific contribution to the water-maze spatial learning task remains unknown. D1R-and D5R-specific in situ hybridization probes showed that forebrain restricted D1R and D5R KO mice (F-D1R/D5R KO) displayed D1R mRNA deletion in the medial (m)PFC, dorsal and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Startle response and pre-pulse inhibition are normal in these mice. Memory assessing paradigms (Morris water maze, and cued and contextual fear conditioning) are also not altered 17,21 , however, when probed more thoroughly, such as for example in a paired-trial T-maze test and a temporal order object recognition task, the KO mice exhibited reduced performance 22 .…”
mentioning
confidence: 95%
“…Startle response and pre-pulse inhibition are normal in these mice. Memory assessing paradigms (Morris water maze, and cued and contextual fear conditioning) are also not altered 17,21 , however, when probed more thoroughly, such as for example in a paired-trial T-maze test and a temporal order object recognition task, the KO mice exhibited reduced performance 22 .…”
mentioning
confidence: 95%
“…In mammals many studies have shown a prominent role of dopamine signalling in hippocampal-dependent memory tasks including LTM 48 49 , through D1-class receptors 50 51 52 , but without discriminating the involvement of D1 or D5 receptors. A couple of recent reports have started to investigate the role of either receptor type separately, revealing that both may actually be involved, but their respective functional roles remains to be clarified 52 53 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not perform direct comparisons between the DH and RSC (because the experiments were performed separately, at different times, and in different behavioral rooms, resulting in different freezing levels in vehicle controls), the observed effects point toward a model of muscarinic contribution to retrieval that is multifaceted and non-uniform across brain regions. Unlike other neurotransmitter receptors such as NMDAR (Gao et al 2010), AMPA receptors (Schiapparelli et al 2006;Bannerman 2009), adrenergic receptors (Gibbs and Summers 2002;Galeotti et al 2004), and dopamine receptors (Sarinana et al 2014;Sarinana and Tonegawa 2016) for which the roles of specific receptor subunits or subtypes are clearly discriminable in various memory processes, it seems that activation of several mAChR subtypes may be necessary to maximally effect one process. This model is consistent with findings using electrophysiological approaches, which demonstrate that cortical M 1 , M 2 , and M 4 together exert a "triad of effects" (M 1 increases neuronal firing rates, M 2 mediates a decrease in cellular inhibition, and M 4 depresses excitatory transmission), which may underlie attention and learning (Gigout et al 2012).…”
Section: Discussionmentioning
confidence: 99%